(untitled) (Journal of Ideas in Health, 2023)
Background: One of the most significant and perilous challenges faced by African societies, including Tanzania, is the public health threat posed by zoonotic viruses. This study aimed to ascertain the presence of viruses in wild rodents, domestic dogs, and humans who shared the same environment. Methods: A cross-sectional study was conducted in the Ngorongoro district from January to September 2022. Metagenomics next-generation sequencing technologies, including Illumina (MiSeq) and Oxford Nanopore (MinION), were employed to identify viruses in 530 blood samples collected from 200 humans, 230 wild rodents, and 100 domestic dogs. The captured wild rodents belonged to various species: Mastomys spp (n=87), Ratus spp (n=45), Avicanthis spp (n=40), Arcomys spp (n=28), Mus spp (n=16), and Field mice (n=14). The taxonomic classification of viruses was carried out using the Kraken2 program. Results: A total of 20 RNA and 20 DNA viral families were detected. Zoonotic RNA families identified in rodents included Peribunyaviridae, Hantaviridae, Flaviviridae, Coronaviridae, Orthomyxoviridae, Paramyxoviridae, Retroviridae, Picornaviridae, Arenaviridae, Togaviridae, and Tobaniviridae. The zoonotic DNA families detected in rodents were Adenoviridae, Poxviridae, Herpesviridae, Anelloviridae, and Circoviridae. Peribunyaviridae and Hataviridae were identified in both humans and rodents. Unclassified +ssRNA viruses were found in dogs and humans. Herpesviridae was present in all three hosts. When compared to dogs and humans, rodents harbored zoonotic viruses that pose a significant public health safety concern. Conclusion: The study unveiled a noteworthy pattern where the majority of RNA and DNA viruses with zoonotic potential were detected in wild rodents, as opposed to dogs and humans. These findings underscore the pivotal role played by wild rodent populations in the transmission and maintenance of such viruses.